2018
DOI: 10.1159/000491972
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered DC-Targeting Lentivector Induces Robust T Cell Responses and Inhibits HBV Replication in HBV Transgenic Mice via Upregulating T Cell Autophagy

Abstract: Background/Aims: Developing engineered dendritic cell (DC)-targeting lentivectors (LVs) have been the target of intense research for their potential to create antigen-directed immunotherapeutics which can be safely administered to patients. In this study, we constructed a DC-directed LV (LVDC-UbHBcAg-LIGHT) as a potential vaccine to induce anti-HBV immune responses. Methods: Specificity of LVDC-UbHBcAg-LIGHT for DCs in vivo was confirmed through live animal imaging studies. The levels of cytokine production in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Autophagy was regarded as a remarkable contributor to HBV replication, confirmed via independent studies showing that autophagy inhibition strongly impaired replication of HBV in liver cells . Furthermore, it has been shown that autophagy deficiency noticeably represses HBV replication in transgenic mice and that autophagy was necessary for HBV envelopment, despite being unnecessary for HBV release . Our research shows that miR‐155 positively modulated HBV replication, similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy was regarded as a remarkable contributor to HBV replication, confirmed via independent studies showing that autophagy inhibition strongly impaired replication of HBV in liver cells . Furthermore, it has been shown that autophagy deficiency noticeably represses HBV replication in transgenic mice and that autophagy was necessary for HBV envelopment, despite being unnecessary for HBV release . Our research shows that miR‐155 positively modulated HBV replication, similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…As an APC, DCs can absorb and process HBsAg and secrete a variety of cytokines to participate in the regulation of immune tolerance and immune responses in patients with chronic HBV infection [ 77 ]. At the same time, the liver contains different nonparenchymal cell populations, which can also be used as APCs.…”
Section: Formation Mechanism Of Persistent Low-level Hbsag Expressionmentioning
confidence: 99%
“…Autophagy is essential for HBV-specific adaptive immune responses. Ma et al demonstrated the ability of a lentivector-targeting engineered dendritic cell (DC) to induce robust T-cell responses and elicit effective anti-HBV effect in HBV transgenic mice [68,69]. They further revealed that the upregulation of the autophagy of T cells aids in the eradication of HBV by promoting the survival and proliferation of activated CD8 + T cells.…”
Section: Autophagy Regulates Hbv-related Immune Responsesmentioning
confidence: 99%
“…Ma et al constructed a DC directed against a lentivector (LV) (LVDC-UbHBcAg-LIGHT) for use as a potential vaccine to induce anti-HBV immune responses. They found that the vaccine elicited effective anti-HBV effects in HBV transgenic mice [68,69]. Further study revealed that the increased autophagy of T cells primarily contributed to the elimination of HBVs.…”
Section: Autophagy-based Anti-hbv Strategiesmentioning
confidence: 99%